Determinants Analysis Factors Affecting the Capability of Family Healthcare of Chronic Kidney Disease with Hemodialysis - Faridah, Virgianty Nur; Nursalam, Nursalam; Kurniawati, Ninuk Dian; Maghfiroh , Isni Lailatul (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Family members have an important role in the healthcare of other family members, especially for hemodialysis patients. AIM: The purpose of this study is to analyze the determinants of factors that affect the ability of families to care for patients of chronic kidney disease (CKD) with hemodialysis. METHODS: This research was used descriptive-analytical with a cross-sectional approach. The utilized population was families of CKD patients with hemodialysis in three hospitals in East Java, Indonesia. Through multistage random sampling, 155 families were obtained. The research data were taken with family questionnaire, patient questionnaire, social support questionnaire, and health-care services questionnaire. After tabulating the data, the hypothesis was tested with Structural Equation Modeling-Partial Least Squares with a significance level of ≤ 0.05 or the value of t-statistic ≥t-table (1.96). RESULTS: The results showed that the family factors (t = 2.527) with six indicators (Age, education, family structure and function, motivation, experience and skill, and knowledge) had a strong effect on family health-care ability, with p = 0.012. The patient factors (t = 2.355) with four indicators (physical, psychological condition, lenght of care, and disease severity) had a strong effect on family health-care ability, with p = 0.019. The social support factor (t = 8.051) with three indicators (family, peer, and health-care support) had a strongest effect on family health-care ability, with p = 0.000. The health service factor (t = 2.820) had a strong effect on family health-care ability, with p = 0.005. CONCLUSION: Based on those results, it becomes necessary to increase the knowledge of family members. Besides that, improve the physical and psychological condition of patients by involving support from peer groups and health workers can be done. The quality of health services must also improved so the family’s health-care ability of CKD patients with hemodialysis can increase.